Heavy precipitation as a risk factor for shigellosis among homeless persons during an outbreak — Oregon, 2015–2016. Issue 3 (March 2018) - Hines, Jonas Z.; Jagger, Meredith A.; Jeanne, Thomas L.; West, Nicole; Winquist, Andrea; Robinson, Byron F.; Leman, Richard F.; Hedberg, Katrina
Highlights: During 2015–2016, a multistate outbreak of Shigella occurred among MSM. In Oregon, the outbreak spread from MSM to homeless persons. Among homeless persons, precipitation was associated with Shigella sonnei transmission. Precipitation could have worsened poor sanitary conditions and increased crowding. Abstract: Objectives: Shigella species are the third most common cause of bacterial gastroenteritis in the United States. During a Shigella sonnei outbreak in Oregon from July 2015 through June 2016, Shigella cases spread among homeless persons with onset of the wettest rainy season on record. Methods: We conducted time series analyses using Poisson regression to determine if a temporal association between precipitation and shigellosis incidence existed. Models were stratified by housing status. Results: Among 105 infections identified, 45 (43%) occurred in homeless persons. With increasing precipitation, cases increased among homeless persons (relative risk [RR] = 1.36 per inch of precipitation during the exposure period; 95% confidence interval [CI] = 1.17–1.59), but not among housed persons (RR = 1.04; 95% CI 0.86–1.25). Conclusions: Heavy precipitation likely contributed to shigellosis transmission among homeless persons during this outbreak. When heavy precipitation is forecast, organizations working with homeless persons could consider taking proactive measures to mitigate spread of enteric infections.